2019
DOI: 10.1002/cctc.201900293
|View full text |Cite
|
Sign up to set email alerts
|

Functional Applications of Metallic Glasses in Electrocatalysis

Abstract: Metallic glasses (MGs), which are also known as amorphous metals, are formed by quenching the melts at a super high cooling rate (e. g. 106 K/s) to avoid crystallization. Compared with ordinary metals, there is no long‐range translational order and crystalline defects in MGs. Benefitting from this unique structural characteristic, MGs show many superior mechanical, physical and chemical properties and thus have been attracting intensive attentions in applications as structural materials. The investigations on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
29
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(29 citation statements)
references
References 78 publications
0
29
0
Order By: Relevance
“…6 Hydrogen intake also changes the electronic structure, rendering asymmetric peaks at Pd 3d3/2 and 3d5/2 orbitals. 6 Interestingly, as opposed to the electrocatalytic hydrogen activity deterioration of Pt/C or Mo2C/C electrodes, Pd40Ni10Cu30P20 MG ribbons, 7,8 nanoporous Pd-Cu-S, 9 Pd-Ru nanoparticles, 10 Pd-Ni-P MG with micro/nano hierarchical porous structure, 8,11 and Pd-Si-Cu thin films in our previous study 12 shows a remarkable improvement as the number of CV cycles increases. Similar to high entropy alloys, [13][14][15] Pd-Ni-Si-P MG with hierarchical nanostructures, 8,16 Pd40Ni10Cu30P20 MG ribbons, 7,8 and nanoporous amorphous Pd-Cu-S 9 show a self-stabilizing behavior under long-term static overpotentials.…”
Section: Accepted Manuscriptmentioning
confidence: 66%
“…6 Hydrogen intake also changes the electronic structure, rendering asymmetric peaks at Pd 3d3/2 and 3d5/2 orbitals. 6 Interestingly, as opposed to the electrocatalytic hydrogen activity deterioration of Pt/C or Mo2C/C electrodes, Pd40Ni10Cu30P20 MG ribbons, 7,8 nanoporous Pd-Cu-S, 9 Pd-Ru nanoparticles, 10 Pd-Ni-P MG with micro/nano hierarchical porous structure, 8,11 and Pd-Si-Cu thin films in our previous study 12 shows a remarkable improvement as the number of CV cycles increases. Similar to high entropy alloys, [13][14][15] Pd-Ni-Si-P MG with hierarchical nanostructures, 8,16 Pd40Ni10Cu30P20 MG ribbons, 7,8 and nanoporous amorphous Pd-Cu-S 9 show a self-stabilizing behavior under long-term static overpotentials.…”
Section: Accepted Manuscriptmentioning
confidence: 66%
“…Chemically complex catalytic materials have been the subject that attracts tremendous research interest in materials science and engineering. [ 1–3 ] By increasing the chemical complexity of modern catalytic materials, it has been shown that superior properties could be achieved for their use in a variety of important applications, such as wastewater remediation, [ 4–8 ] catalysis, [ 9,10 ] energy storage, [ 11 ] and fuel cells. [ 12 ] Recently, a similar design principle was proposed by metallurgists to enhance the chemical complexity of alloys through the synthesis of multi‐principal element alloys, also known as high entropy alloys (HEAs), [ 13,14 ] for enhanced mechanical properties.…”
Section: Introductionmentioning
confidence: 99%
“…22 Amorphous alloys or metallic glasses (MG's) have attracted researchers' signicant interest as a structural material due to their superior mechanical properties, and recently excellent catalytic activities of these alloys were also reported. [23][24][25] Metallic glasses (MG's) with good intrinsic electrical conductivity are also suggested to be better electrocatalyst due to their corrosive resistant properties, free-standing nature in electrolyte solutions, metastable nature leading to high catalytic activity and industrially feasible production. 26,27 The limitations of noble metal-based electrocatalysts led researchers to try transition metals like Fe, Co, Ni-based metallic glass as an alternative.…”
Section: Introductionmentioning
confidence: 99%